2023
DOI: 10.3389/fonc.2023.1210314
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 ultra-low breast cancer: exploring the clinicopathological features and prognosis in a retrospective study

Jiajie Shi,
Liqiu Zhang,
Cuizhi Geng

Abstract: ObjectiveTo explore the clinicopathological features of patients with ultra-low expression of human epidermal growth factor 2 (HER-2) in breast cancer and its impact on prognosisMethodsData from 1024 patients with primary breast cancer having HER-2 ultra-low expression from January 01, 2018, to December 31, 2018, were collected and analyzed retrospectively. The clinicopathological features and prognosis were compared using a chi-squared test or Fisher exact probability method. COX regression analysis and log-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our findings corroborate the research performed by Mahmood et al, which noted the strong impact of tumor diameter on survival and reported that more patients with tumor diameter ≤ 2 cm presented an overall survival of more than ten years [20]. Furthermore, Shi et al noted that lymph node metastasis, tumor diameter, and Ki67 expression were risk factors affecting the 5 year DFS rates in patients with ultra-low HER2 expression [21]. The above-mentioned studies emphasize the importance of commonly used clinicopathological biomarkers as still valid and relevant prognostic factors.…”
Section: Tumor Diameter As a Prognostic Indicator Of Survivalsupporting
confidence: 92%
“…Our findings corroborate the research performed by Mahmood et al, which noted the strong impact of tumor diameter on survival and reported that more patients with tumor diameter ≤ 2 cm presented an overall survival of more than ten years [20]. Furthermore, Shi et al noted that lymph node metastasis, tumor diameter, and Ki67 expression were risk factors affecting the 5 year DFS rates in patients with ultra-low HER2 expression [21]. The above-mentioned studies emphasize the importance of commonly used clinicopathological biomarkers as still valid and relevant prognostic factors.…”
Section: Tumor Diameter As a Prognostic Indicator Of Survivalsupporting
confidence: 92%
“…The progesterone receptor was also positive in most cases (162, 67,4%). 4 Chen et al Considering the previously described studies, there was a mild variation about age. In all populations, most of the tumors were positive to ER an PR.…”
Section: Methodsmentioning
confidence: 97%
“…In the included population, age, histologic subtype and immunohistochemical data for the estrogen receptor, progesterone receptor and KI-67 (<20% x ≥20%) were assessed. 4,7,8 The data was evaluated by two pathologists, following the recommendations for immunohistochemical tests of following the recommendations for immunohistochemical tests of estrogen and progesterone receptors in breast cancer. 9 Paraffin samples were subjected to immunohistochemistry for Estrogen Regarding immunohistochemical receptors, the estrogen receptor was positive in most of the sample (182, 73,1%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations